Antimony oxychloride/graphene aerogel composite as anode material for sodium and lithium ion batteries. (May 2018) - Lakshmi, K.P.; Janas, K.J.; Shaijumon, M.M.
Abstract: Herein, we report on the synthesis of phase-pure antimony oxychloride (Sb4 O5 Cl2 ) microstructures and studies on their electrochemical properties as new and potential anodes for sodium and lithium ion batteries. We demonstrate that pristine Sb4 O5 Cl2 based electrode exhibits promising electrochemical behaviour, with a reversible discharge capacity of 830 mAh g −1 for the first cycle when cycled against sodium at a current rate of 30 mA g −1 . Further, a composite of graphene aerogel is prepared with Sb4 O5 Cl2 microstructures, which are uniformly anchored on the graphene aerogel matrix (Sb4 O5 Cl2 -GA), resulting in interconnected networks which facilitate better charge transfer and effective buffering to alleviate the structural variation of Sb4 O5 Cl2 during cycling. We show that Sb4 O5 Cl2 -GA electrode exhibits excellent electrochemical properties with much improved cyclic stability and high rate capability. In addition, Sb4 O5 Cl2 -GA delivers excellent performance as anode material for lithium ion batteries, with a reversible capacity of 600 mAh g −1 obtained over 50 cycles, at a current rate of 50 mA g −1 . The obtained results are promising and demonstrate 3D networked antimony oxychloride/graphene composite as a potential anode material for both lithium and sodium ion batteries. Graphical abstract: Image 1